Melatonin for the Management of Preeclampsia: A Review - Annie Langston-Cox; Sarah A. Marshall; Daisy Lu; Kirsten R. Palmer; Euan M. Wallace (MDPI AG, 2021)
Preeclampsia is a disease specific to pregnancy characterised by new-onset hypertension with maternal organ dysfunction and/or fetal growth restriction. It remains a major cause of maternal and perinatal morbidity and mortality. For sixty years, antihypertensives have been the mainstay of treating preeclampsia and only recently have insights into the pathogenesis of the disease opened new avenues for novel therapies. Melatonin is one such option, an endogenous and safe antioxidant, that may improve the maternal condition in preeclampsia while protecting the fetus from a hostile intrauterine environment. Here we review the evidence for melatonin as a possible adjuvant therapy for preeclampsia, including in vitro evidence supporting a role for melatonin in protecting the human placenta, preclinical models, vascular studies, and clinical studies in hypertension and pregnancy.